Systemic lupus erythematosus patient on steroid therapy that develop to a Stevens-Johnson syndrome: a case report - Suardamana, Ketut; Kurniari, Pande Ketut; Winangun, I. Made Arya (International Journal of Advances in Medicine, 2022)
Stevens-Johnson syndrome (SJS) is a cutaneous immunity reaction involving the skin and mucosa and is an emergency condition that can be fatal. The incidence of this disease is relatively rare in the range of 1-2 per 1.000.000 population. The pathogenesis of SJS involves the immune system response of antigenic drug to body tissues but it still cannot be fully explained to date. We reported a woman, 35 years old with systemic lupus erythematosus (SLE) who had been on steroid therapy and in the course of treatment developed into SJS after administration of anti-epileptic drug. Steroids have anti-inflammatory effects mainly due to decreased syntheses or suppression of inflammatory mediators. SJS still can develop in patient with SLE who had been on steroid therapy. Giving steroid that indicated for the treatment of a disease including SLE, cannot prevent the occurrence of an allergic event including SJS. The presence of steroid can extend the duration of starting the drug with the occurrence of SJS and reduce the severity of the disease. Steroid still have a role in treatment that can be used both in SJS and SLE.